2016
DOI: 10.1007/s00420-016-1115-9
|View full text |Cite
|
Sign up to set email alerts
|

Road traffic noise, air pollution and myocardial infarction: a prospective cohort study

Abstract: This study did not provide evidence for an increased risk of MI due to exposure to road traffic noise or air pollution at moderate average exposure levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 28 publications
8
34
0
Order By: Relevance
“…per 10 dB L den for IHD following exposure to noise from road traffic (van Kempen et al, 2017). In our study, the overall result was comparable to a recent Swedish cohort study on myocardial infarction and road traffic noise showing a RR of 0.99 (95% CI 0.86-1.14) per 10 dB L den (Bodin et al, 2016). For IHD mortality our results are similar to the WHO-review reporting a pooled RR of 1.05 (95% CI 0.97-1.13) per 10 dB L den based on 1 case-control and 2 cohort studies.…”
Section: Ischemic Heart Disease and Strokesupporting
confidence: 87%
“…per 10 dB L den for IHD following exposure to noise from road traffic (van Kempen et al, 2017). In our study, the overall result was comparable to a recent Swedish cohort study on myocardial infarction and road traffic noise showing a RR of 0.99 (95% CI 0.86-1.14) per 10 dB L den (Bodin et al, 2016). For IHD mortality our results are similar to the WHO-review reporting a pooled RR of 1.05 (95% CI 0.97-1.13) per 10 dB L den based on 1 case-control and 2 cohort studies.…”
Section: Ischemic Heart Disease and Strokesupporting
confidence: 87%
“…A recent meta-analysis of three cohorts and four case-control studies calculated a Relative Risk (RR) of 1.08 (95% CI 1.01 to 1.15) per 10 dB L den for IHD following exposure to noise from road traffic 2. In the present study, the overall result was comparable to a recent Swedish cohort study on myocardial infarction and road traffic noise showing a RR of 0.99 (95% CI 0.86 to 1.14) per 10 dB L den 15. For IHD mortality, our results were similar to the WHO-review reporting a pooled RR based on one case-control and two cohort studies of 1.05 (95% CI 0.97 to 1.13) per 10 dB L den .…”
Section: Discussionsupporting
confidence: 71%
“…Associations between air pollution and subclinical atherosclerosis support this (Kaufman et al 2016;Künzli et al 2010;Sun et al 2005). Although the lack of observed effects for any pollutant on overall MI incidence in multiple large epidemiological studies is noteworthy (Atkinson et al 2013;Bodin et al 2016;Lipsett et al 2011;Miller et al 2007;Puett et al 2011Puett et al , 2009Puett et al , 2008Rosenlund et al 2006;Stockfelt et al 2015), recent evidence of an association between those particles capable of entering the bloodstream, PM 2:5 (Bai et al 2019a;Danesh Yazdi et al 2019;Klompmaker et al 2019;Yusuf et al 2020) and UFPs (Bai et al 2019b;Downward et al 2018), and incident MI supports this mechanistic evidence. This may imply that air pollution-promoted atherosclerosis leads to a more severe subtype of ischemic event that results in death.…”
Section: Discussionmentioning
confidence: 78%
“…A number of studies have detected significant positive associations between MI incidence and air pollutants such as nitrogen dioxide (NO 2 ) (Grazuleviciene et al 2004;Rosenlund et al 2009;Roswall et al 2017) and particulate matter (PM) with a diameter <2:5 lg=m 3 (PM 2:5 ) (Bai et al 2019a;Danesh Yazdi et al 2019;Klompmaker et al 2019;Madrigano et al 2013;Yusuf et al 2020), <10 lg=m 3 (PM 10 ) (Rosenlund et al 2009), or <0:1 lg=m 3 [ultrafine particles (UFPs)] (Bai et al 2019b;Downward et al 2018). However, in many of the aforementioned, and other, studies, associations for NO 2 (Atkinson et al 2013;Bai et al 2019aBai et al , 2019bDownward et al 2018;Lipsett et al 2011;Rosenlund et al 2006), PM 2:5 (Downward et al 2018;Lipsett et al 2011;Miller et al 2007;Puett et al 2011Puett et al , 2009, PM 10 (Atkinson et al 2013;Downward et al 2018;Klompmaker et al 2019;Lipsett et al 2011;Puett et al 2011Puett et al , 2008Rosenlund et al 2006), and nitrogen oxides (NO x ) (Bodin et al 2016;Downward et al 2018;Lipsett et al 2011;Stockfelt et al 2015) have been null or nonsignificant. Notably, those studies that examined nonfatal and fatal MI incidence separately reported stronger associations with fatal MI for NO 2 (Rosenlund et al 2009(Rosenlund et al , 2006Roswall et...…”
Section: Introductionmentioning
confidence: 99%